Quality Enhancement of Aceh Swamp Buffalo (Bubalus bubalis) Frozen Semen by Supplementing β-Carotene - K. Eriani; A. Azhar; M. Ihdina; B. Rosadi; M. Rizal; A. Boediono (Tropical Animal Science Journal, 2018)
Sperms are vulnerable to oxidative stress due to the high proportion of polyunsaturated fatty acids within their membranes. This condition could decrease sperms quality during preservation. β-carotene is among antioxidants able to neutralize reactive oxygen species, natural by-products of oxygen metabolism in sperms. This study was done to investigate the capability and protective effect of this antioxidant on motility, viability, acrosomal integrity, and plasma membrane integrity of frozen-thawed sperms of Aceh swamp buffalo. The study was conducted using completely randomized design with four treatments and five replications. Fresh semen was diluted in egg-yolk tris-based extenders with the addition of antioxidant of 0% (w/v) (control, P0), 0.625% (w/v) (P1), 1.25% (w/v) (P2), and 2.5% (w/v) (P3) prior to freezing. Variables of sperms quality examined were  motility, viability, acrosomal integrity, and plasma membrane integrity of semen after dilution, equilibration, and thawing. Semen having the best post-thawing quality after β-carotene treatment was used for artificial insemination (AI) for accessing its pregnancy rate. The results showed that the addition of 0.625% (w/v) β-carotene (P1) resulted in the highest motility, viability, acrosomal integrity, and plasma membrane integrity. Pregnancy rate of buffalo inseminated with semen treated with 0.625% β-carotene (P1) was 50%. In conclusion, administration of 0.625% β-carotene was able to maintain and could protect motility, viability, acrosomal integrity, and plasma membrane integrity of frozen sperms of Aceh swamp buffalo that are good for artificial insemination.